Effect of The Use of Diesel-Biodiesel on Air Emissions and Exhaust Gas Opacity of Mining Equipment in West Banko IUP - PT Bukit Asam Tbk - Setiyawan, Bambang Dwi; Hariani, Poedji Loekitowati; Komariah, Leily Nurul (Sriwijaya Journal of Environment, 2024)
PT Bukit Asam Tbk has adopted the use of plant-based diesel oil in compliance with the rules established by the Minister of Energy and Mineral Resources No. 12 of 2015 from previously using fossil diesel. One of the decarbonization program's initiatives to reduce emissions is to replace the use of fossil fuels with biodiesel for all production equipment. To obtain results on the decrease or increase in the environmental quality of the use of fossil fuels and biodiesel, this research requires comparative data obtained from the results of ambient air quality, emissions, and opacity test. Based on research data in the years 2018 – 2022, the emission quality test was obtained with an average CO parameter of 550.83 mg/nm3, which exceeded the quality standard of 540 mg/nm3, SO2 parameter of 79.03 mg/nm3 from the quality standard of 900 mg/nm3. The NO2 parameter is 161.29b mg/nm3 from the quality standard of 1200 mg/nm3, with the quality standard parameters referring to thw Minister of Environment and Forestry Regulation No. 15 of 2019. Based on quantitative analysis approaches method and trend analysis obtained the emission results experienced an increase with trend line analysis but were still below the quality standards. The results at IUP Banko Barat for mobile equipment sources were obtained at 5.23% HSU, while for static equipment sources, they were obtained at 9.88% HSU from the quality standard of 40% based on South Sumatera Governor Regulation No. 06 of 2016. It can be concluded that the variance of fuel use for the 2018-2022 period has no significant effect on the air quality test emissions and opacity results because it is still below the quality standard.